2018
DOI: 10.1080/13697137.2018.1493451
|View full text |Cite
|
Sign up to set email alerts
|

Association of serum ferritin levels with non-alcoholic fatty liver disease in postmenopausal women

Abstract: The serum ferritin level was positively and independently associated with NAFLD in postmenopausal women and could be a useful additional measure in assessing the risk of NAFLD in postmenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Liver biopsies of 222 patients (men and women) with NAFLD showed that serum ferritin levels, which are biomarkers of iron metabolism, are positively associated with a higher NAFLD activity score [316]. The relation between ferritin level and NAFLD is mostly significant in men and associated with hepatic iron deposition, fibrosis, and NASH [77,317]. A correlation between ferritin level and NAFLD development also has been observed in a cohort of postmenopausal women [317].…”
Section: Dietary Oxidants In Nafldmentioning
confidence: 90%
See 1 more Smart Citation
“…Liver biopsies of 222 patients (men and women) with NAFLD showed that serum ferritin levels, which are biomarkers of iron metabolism, are positively associated with a higher NAFLD activity score [316]. The relation between ferritin level and NAFLD is mostly significant in men and associated with hepatic iron deposition, fibrosis, and NASH [77,317]. A correlation between ferritin level and NAFLD development also has been observed in a cohort of postmenopausal women [317].…”
Section: Dietary Oxidants In Nafldmentioning
confidence: 90%
“…The relation between ferritin level and NAFLD is mostly significant in men and associated with hepatic iron deposition, fibrosis, and NASH [77,317]. A correlation between ferritin level and NAFLD development also has been observed in a cohort of postmenopausal women [317].…”
Section: Dietary Oxidants In Nafldmentioning
confidence: 93%
“…The prevalence of NAFLD was up to 30% in the general population and 26.3% in men [35]. In postmenopausal women, the prevalence of NAFLD was up to approximately 40%, which suggested a greater importance of NAFLD for postmenopausal women [6]. The development of NAFLD is also closely correlated with several chronic diseases, such as obesity, type 2 diabetes mellitus, dyslipidemia, and hypertension, which are components of metabolic syndrome (MetS) [79].…”
Section: Introductionmentioning
confidence: 99%
“…Two cross-sectional studies also showed that higher serum ferritin was associated with a higher risk of NAFLD and elevated ALT among Chinese adults with normal weight [25,26]. In addition, a Korean study conducted on postmenopausal women found that the serum ferritin level was positively and independently associated with NAFLD [27]. Most cross-sectional studies reported a positive association between serum ferritin levels and the prevalence of NAFLD, however, cross-sectional study designs cannot be used to determine causal relationships because temporality is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional and case-control studies have assessed the association between serum ferritin levels and the risk of NAFLD [24][25][26][27]. Recent a cross-sectional study found that serum ferritin positively associated with alanine aminotransferase (ALT) among subjects with overweight/obesity and ultrasound-con rmed liver steatosis [24].…”
Section: Discussionmentioning
confidence: 99%